Sorption of Chromium(Vi) and Copper(Ii) from Aqueous Solution by Chemically-Modified Rice Hull - Tan, Hong Sun (2004)
The sorption of Cr(VI) and Cu(II) from single and binary metal solutions by rice hull modified using different chemical reagents were investigated. Modification of rice hull using citric acid and quaternary ammonium salt was investigated and optimized to yield a material (citric acid-quaternized rice hull – CQRH) which was capable of removing both Cr(VI) and Cu(II) simultaneously and efficiently.